Étude de la relation entre le climat de la classe et la satisfaction des étudiants dans un contexte universitaire - Busugutsala, Gandayi Gabudisa (Canadian Journal of Higher Education, 2017)
This article presents partial results of a global study about the relation between the class climate and the learning in a university context. Learning is a complex process of involvement and total development of the students. This happens in a rich environment of roles and interactions. We are presenting one of the learning indicators: the students’ satisfaction. On one hand, results confirm that there is a relation between the class climate the students’ varied levels of satisfaction. On the other hand, the class climate varies like its direct influence or as a variable mediator between the students’ and the professors’ characteristics versus the learning process.